Julia : high performance programming : learning path : leverage the power of Julia to design and develop high performing programs /: high performance programming : learning path : leverage the power of Julia to design and develop high performing programs. (2016) - Balbaert, Ivo; Sengupta, Avik; Sherrington, Malcolm
No abstract available